PERENCANAAN STRUKTUR APARTEMEN WHITE PEARL SEMARANG - David Mulyawan Prayogo; Dea Nika Alvianti; Nuroji Nuroji; Himawan Indarto (Jurnal Karya Teknik Sipil, 2013)
Structural analysis calculations of White Pearl apartment buildings against earthquake load refers to Earthquake Resilience Planning Procedures for Building Structures and Non-Building (SNI 1726-2012), where the analysis of the seismic load high-rise building structures made with Spectrum Analysis Method Dynamic Response. White Pearl apartment building belonging to the Seismic Design Criteria for Type D with high seismic risk level, so the building frame structure configuration bearers that used is Special Moment Frame System (SRPMK). SRPMK system is designed so that the building does not collapse or collapse during an earthquake in excess of the earthquake that has been designed, therefore SRPMK models are designed in order to qualify strong columns weak beams. System with method strong column weak beam does not mean in the literal sense, but rather a column designed to hold the beam at the beam having plastic hinge. At SRPMK models are designed so that plastic joints located at a certain point. Joint at the beam-column relations should also be designed properly to avoid collapse first. This Apartment has a asymmetrical shape, so when there was an earthquake the building will undergo rotational that is caused by the center of stiffness and the center of mass is not located in one spot, so it needs dilatation so that the center of mass and the center of stiffness to coincide. This apartment building has a slim shape, therefore necessary to check the drift story in order to the floor shake is not too big.